Healthy lifestyle and common mental disorders (CMD) in the context of COVID-19 (Research, Society and Development, 2023)
Objective: to analyze the mediating effect of a healthy lifestyle on the mental health of participants in a Virtual Health Fair, during the COVID-19 pandemic. Methodology: Cross-sectional of 1,029 people aged 18 years and over. The Virtual Health Fair was organized as a tridimensional, and data were collected through a link on Google Forms, containing the sociodemographic data form, the Eight Natural Remedies Questionnaire (Q8RN), and the Common Mental Disorders questionnaire (SRQ-20). A Structural Equation Modeling (SEM) was performed. Results: Most participants were female (69%; n= 729), married (53.5%; n= 565), of higher education (43.2%; n= 458), and Adventist in religious affiliation (56.7%; n=597). On average, lifestyle was categorized as good by the Q8RN score (mean 56.61; SD 11.59), with a deficiency in the practice of exercise (5.87; 4.02). The Body Mass Index (BMI) was overweight on average (mean 26.02; SD 5.24). A prevalence of common mental disorders was 30.2% based on the SRQ-20 questionnaire. Conclusion: Results indicated that BMI, age, education, and religion had a strong protective effect (62%, p